EVALUATION OF THE SiMBA (SIKAP MODERASI BERAGAMA) LEARNING MEDIA SOCIALIZATION PROGRAM IN TUNGGULWULUNG, MALANG CITY - Prabowo, Cahyaningtias Dwi; Nabiel Mumtaz Zaydane Firdaus; Rafi Nur Rais; Barokah Ulfah Luqyana; Taufik Hidayatullah; Royhanah Nuqoyyah Thoyyibah; Khotibul Umami; Anisahyumnah Nurnabilah; Putri Noviani; Avril Noer Utami Insani (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Religious moderation has an important role in maintaining stability, tolerance, and harmony between religious communities. One method that can be used to convey the value of religious moderation to society is socialization. The implementation of socialization on religious moderation in Tunggulwulung Village, Malang City uses SiMBA (Sikap Moderasi Beragama) media, namely the FGD (forum group discussion) model. This research aims to evaluate the religious moderation socialization program. The method used in this research is a qualitative method with the CIPP model (context, input, process, product). The results and discussion in this research state that the socialization of religious moderation activities using SiMBA media in Tunggulwulung Village, Malang City is going well according to its aim, namely providing deeper knowledge to the local community regarding religious attitudes. moderation. Based on this, SiMBA media can be developed and socialized to the wider community. Meanwhile, this research concludes that the SiMBA socialization media program can be said to be successful based on the context evaluation, input evaluation, process evaluation, and product evaluation carried out during the research.